2014
DOI: 10.1021/bi400604t
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Substrate Binding-Induced Zwitterion Formation in the Catalytic Cys-His Dyad of the SARS-CoV Main Protease

Abstract: The coronavirus main protease (M(pro)) represents an attractive drug target for antiviral therapy of coronavirus (CoV) infections, including severe acute respiratory syndrome (SARS). The SARS-CoV M(pro) and related CoV proteases have several distinct features, such as an uncharged Cys-His catalytic dyad embedded in a chymotrypsin-like protease fold, that clearly separate these enzymes from archetypical cysteine proteases. To further characterize the catalytic system of CoV main proteases and to obtain informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
119
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(134 citation statements)
references
References 128 publications
10
119
2
Order By: Relevance
“…On the other hand, the regulation of M pro activity was investigated to gain a deeper understanding of the cleavage mechanism. First, it was found that the protease activity of M pro could be related to its homodimerization in some way [15,16]. Then, long-distance communication was identified as a temperature-sensitive defect mutant in V184 or F219 could be readily recovered by a second-site mutation (S133 N or H134Y) [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the regulation of M pro activity was investigated to gain a deeper understanding of the cleavage mechanism. First, it was found that the protease activity of M pro could be related to its homodimerization in some way [15,16]. Then, long-distance communication was identified as a temperature-sensitive defect mutant in V184 or F219 could be readily recovered by a second-site mutation (S133 N or H134Y) [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, CoV infected patients administered with protease inhibitors, lopinavir/ritonavir, have shown improved outcome, [1,13] demonstrating the potential of the main protease (Mpro) as the most promising drug target in CoVs [14,15] Hence, a recently published X-ray crystal structure of the SARS-CoV-2 Mpro provides an excellent ground for structure-based drug discovery efforts. [16] Earlier efforts to target SARS-CoV resulted in identification of several covalent Mpro inhibitors targeting the catalytic dyad of the protein defined by His41 and Cys145 [17] residues. However, covalent inhibitors are often marked by adverse drug responses, off-target side effects, toxicity and lower potency.…”
Section: Introductionmentioning
confidence: 99%
“…Paasche et al have pointed out that the low inhibition potencies of known covalently interacting inhibitors may, at least in part, be attributed to insufficient fostering of the proton‐transfer reaction based on MM/MQ analysis of SARS 3CL pro . Unfortunately, our method of study was incapable of accessing this charge state.…”
Section: Resultsmentioning
confidence: 99%